2014
DOI: 10.1113/jphysiol.2013.264655
|View full text |Cite
|
Sign up to set email alerts
|

Effects of obesity, diabetes and exercise on Fndc5 gene expression and irisin release in human skeletal muscle and adipose tissue: in vivo and in vitro studies

Abstract: Key pointsr Considerable controversy exists regarding the role of irisin, a putative exercise-induced myokine, in human metabolism.r We therefore studied irisin and its precursor Fndc5 in obesity, type 2 diabetes and exercise. r Complex clinical studies combined with cell culture work revealed that Fndc5/irisin was decreased in type 2 diabetes in vivo, but not in muscle cells in vitro, indicating that diabetes-related factor(s) regulate Fndc5/irisin in vivo.r Several attributes of type 2 diabetes, such as hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
340
8
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 361 publications
(385 citation statements)
references
References 28 publications
24
340
8
13
Order By: Relevance
“…Although the skeletal muscle is the tissue with the highest expression of FNDC5/ irisin (2), other tissues, including the adipose tissue, are responsible for secreting irisin (6,7,23). Additionally, the expression of irisin is upregulated in individuals characterized as obese when compared with others who have a normal weight and are anorexic.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although the skeletal muscle is the tissue with the highest expression of FNDC5/ irisin (2), other tissues, including the adipose tissue, are responsible for secreting irisin (6,7,23). Additionally, the expression of irisin is upregulated in individuals characterized as obese when compared with others who have a normal weight and are anorexic.…”
Section: Discussionmentioning
confidence: 98%
“…In sedentary, overweight, and obese individuals, plasma irisin levels were positively associated with maximal contraction force and rate of force development after 12 weeks of resistance and endurance training (23). A decrease in irisin secretion contributes to muscle insulin resistance in high-fat diet mice (28).…”
Section: Discussionmentioning
confidence: 99%
“…Both studies adhere to the ethical guidelines of the 2000 Declaration of Helsinki, and all study participants provided witnessed written informed consent before entering the study. Details of the study groups and the techniques for clinical parameter assessment have previously been published (14,15). Vim expression was analyzed in 24 samples, and the other targets were analyzed in a subpopulation of 16 patients.…”
Section: Human Studiesmentioning
confidence: 99%
“…Some authors have suggested a possible "irisinemia" as a compensatory effect of organism to try maintain the metabolic homeostasis by irisin secretion (27). However, the better hypothesis must be the negative influence of hyperglycemia and serum lipids on FNDC5/irisin levels, since free fatty acid and glucose in vitro stimulation decrease expression/secretion of these peptides (28). Our metabolic results associated a cluster of FNDC5/irisin levels bring similar clinical evidence of this in-vitro study, and consolidate the studies that observed lower levels of FNDC5/irisin correlated with dysfunctions and metabolic diseases (6,8,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Our present results seem to indicate that this negative LPS influence in browning process could also involve a decrease of FNDC5/irisin, one of the main stimulator of these process. Reinforce this idea the higher fat intake in SIG because the increase of fat, specially the saturated type, is related to LPS absorption, thus the LPS increase could be an inhibitor of FNDC5/ irisin, as observed by excess of glucose and free fat acids (28), which could explain the LPS as a negative regulator of browning (33). Previous study found a positive correlation between FNDC5/irisin levels and carbohydrate intake (34), indicated, together with our result that FNDC5/irisin and macronutrients might have an important interaction that certainly needs to be deeply addressed in future researches, as well as better analyze the relationship between FNDC5/irisin and LPS.…”
Section: Discussionmentioning
confidence: 99%